Proceeding of the international symposium on frontiers of collective motions ( CM 2002 ) : (World scientific, 2003)
The physics of nuclear collective motion was pioneered by A Bohr and B R Mottelson 50 years ago. Since then, experimental and theoretical development in this field has been remarkable under the leadership of the Copenhagen group. In the 21st century, a new era has opened up due to the recent developments of experimental facilities, especially radioactive ion beams and large g-ray arrays. Interest in collective motions is now shared in the research of other quantum many-body systems — for example, microclusters and Bose–Einstein condensation. It is therefore timely and important to review the current understanding of collective motions and discuss new directions of future study. The main topics of the symposium include recent theoretical and experimental progress in the understanding of vibrational and rotational motions in nuclei. Collective motions of Bose–Einstein condensation and microclusters are also addressed. The symposium invited several keynote speakers to review and discuss our present understanding and to identify future challenges. Oral presentations are also selected from submitted contributions. This symposium is an opportunity not just to present progress and future prospects but to exchange new ideas and to provoke controversies through intellectual debates.